Pharmacological inhibitors of β-cell dysfunction and death as therapeutics for diabetes - Dalle, Stéphane; Abderrahmani, Amar; Renard, Eric (Frontiers in Endocrinology, 2023)
More than 500 million adults suffer from diabetes worldwide, and this number is constantly increasing. Diabetes causes 5 million deaths per year and huge healthcare costs per year. -cell death is the major cause of type 1 diabetes. -cell secretory dysfunction plays a key role in the development of type 2 diabetes. A loss of β-cell mass due to apoptotic death has also been proposed as critical for the pathogenesis of type 2 diabetes. Death of -cells is caused by multiple factors including pro-inflammatory cytokines, chronic hyperglycemia (glucotoxicity), certain fatty acids at high concentrations (lipotoxicity), reactive oxygen species, endoplasmic reticulum stress, and islet amyloid deposits. Unfortunately, none of the currently available antidiabetic drugs favor the maintenance of endogenous -cell functional mass, indicating an unmet medical need. Here, we comprehensively review over the last ten years the investigation and identification of molecules of pharmacological interest for protecting -cells against dysfunction and apoptotic death which could pave the way for the development of innovative therapies for diabetes.